#TITLE_ALTERNATIVE# - GANDASASMITA (NIM 24895007), SURYO
Reverse osmosis has been used for water desalination. The performance of reverse osmosis membranes is very much determined by both the natural properties of polymeric membrane materials, as well as the properties created through the manufacturing process. The purpose of this research is to study the influence of membrane properties on the membrane performance in relation to its flux and solute rejection in reverse osmosis process. In this study, three membranes were prepared for reverse osmosis application, namely polysulfon membrane (PSf) and cellulose acetate membrane coagulated at 27 and 5 oC (CA27 and CA05, respectively). The CAO5 membrane had the best performance among the three membranes, with reasonable flux and moderate rejection. The PSf membrane had the lowest flux but moderate rejection. And finally, CA27 had the highest flux with temperate rejection. With increased pressure, fluxes tended to increase also, whereas rejections tended to decrease. The greater the concentration of solute became, the lower the flux became. Upon examination of the three membranes, the differences of the membrane material properties became clear. The PSf membrane had the highest Tg and also the highest degree of crystallinity. Both of the cellulose acetate membranes had almost the same degree of crystallinity and Tg. The structure of the three membranes revealed dense membranes and there was differing thickness in the selective layer. Thus, it was clearly shown that there is a correlation between properties of polymer membrane materials and their performance. Each property works in synergy to optimize membrane performance.